The Effect of Student Perception of Teacher Professional Competency On The Result of Geography Learning Class XI Social Science Student’s SMA 12 Sinjai - Nyompa, Sukri; Suprapta, Suprapta; Wahyuni, Sri; Azhim, Muhamad Ihsan (Universitas Negeri Makassar, 2018)
This research aims to find out: 1 Perceptions of student competency) professional teachers; 2) student learning outcomes; 3) influence the perceptions of students on the professional competence of teachers towards learning outcomes students. This research is the research of ex post facto. Free variables i.e. perception of students on the professional competence of teachers and variable is the result of student learning. Student population of Class XI IPS amounted to 49 students, samples taken 100% is 49 students. The collection of data through observation, question form and the documentation value of Deuteronomy daily student. Data analysis using descriptive analysis and inferensial correlation coefficients of determination of Moment, Product, test data, test the normality and simple linear regression linearity. The results showed that: 1) perceptions of students on the professional competence of teachers having an average score of 3.13 percentage with 78.25% higher categories include; student learning outcome 2) has an average of 3.18 with a percentage of 79.5% categories include enough; 3) inferensial analysis results obtained r_hitung (0.511) greater than r_tabel (0,281) with 5% error level. It can be concluded that the perceptions of students on professional competence teachers influential significantly to student learning outcomes of 26.1% and regression equation Ỷ = 55.639 + 0.476 X can be used in prediction of the level of perception of students on professional competence teachers learn if the result is raised or lowered.